CREATIVE ACTIVITY LEVEL OF STUDENTS DETERMINING EXPERIENCE-TEST RESULTS - Yuldosheva Dilfuzakhon Alisher kizi (Scholar Express Journal, 2022)
This article provides information on the analysis of the current level of preparation of students of the higher education institution for the teaching profession, the results of the study of the current state of students' creative competence at the foundational experience stage.
Keywords: competence; creative competence; important levels of creative